(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study aimed to disclose how relatives of cadaverous donors perceive the organ donation process for transplantation. A phenomenological, qualitative research was carried out on the basis of the "situated-phenomenon structure". The statements revealed that, for the relatives of the donors, the process of donation begins with the patients' hospital admission and only ends when they are buried. Furthermore, it is considered bureaucratic, long, consuming and tiring. This situation results in suffering and stress, but there is no regret about the organ donation since, although the pain caused by the loss does not end, the donation initiative comforts and brings satisfaction.